THE COMPARATIVE STUDY ON ARCHITECTURAL TYPO-MORPHOLOGY OF BOROBUDUR-PRAMBANAN TEMPLE AND ANGKOR WAT, CASE STUDY ON MASS ORDER, FLOOR PLAN, FIGURE AND ORNAMENTS - Andreas Martinus ; Rahadhian Prajudi Herwindo (Riset Arsitektur (RISA), 2018)
Abstract- There are allegations that elements of Javanese temples are also can be found at The Angkorian temples because the Java Middle Classic temples are older than Angkorian temples and Jayawarman II lived in Java at that time. This can be proved by a comparative process between the architecture elements: mass, plans, figures and ornaments owned by the temples that represents its era in both kingdom. Angkor Wat is a synthesis of the development in Angkor culture that reach its the peak of glory. Angkor Wat has architectural elements of Java Middle Classic temples, especially Prambanan and Borobudur. This led to the alleged of similarity from architectural elements between the temples in the two kingdoms. This Study approached by quantitative with semi qualitative method. Through the study on the main temple buildings of the Java Middle Classic and the main temples of the Angkor Wat era with purposive sampling in relation of mass, plan, figure, and ornament. Described descriptively.Angkor Wat is generally inspired by Borobudur-Prambanan. Broadly speaking, it shows the similarity of Prambanan-Borobudur architectural elements to Angkor Wat. Angkor Wat is a synthesis of combining the elements (eclecticism) of Borobudur-Prambanan, but Prambanan has stronger element (indoor temple, tower temple, Hindu temple). In principle (mass, plan, and figure) shows the incorporation of Borobudur-Prambanan, but by ornament on its processing indicates there is further development (dominated findings exist but not similar). Key Words: tipo-morphology, comparison, Angkor, Indochina, Java